2017
DOI: 10.3390/nu9060592
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hot and Cold Environments on the Regulation of Energy Balance Following a Single Exercise Session: A Mini-Review

Abstract: Understanding the regulation of human food intake in response to an acute exercise session is of importance for interventions with athletes and soldiers, as well as overweight individuals. However, the influence of hot and cold environments on this crucial function for the regulation of body mass and motor performance has not been summarized. The purpose of this review was to exhaustively search the literature on the effect of ambient temperature during an exercise session on the subsequent subjective feeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Despite its elevation by food intake, circulating PYY can also be increased by exercise and stress [193,194], conditions that also modify the gut microbiota [195,196]. It is important to note that more studies linking changes in PYY and the gut microbiota are needed.…”
Section: Microbiota and The Npy Pyy And Pp: Relevance To Anxiety Anmentioning
confidence: 99%
“…Despite its elevation by food intake, circulating PYY can also be increased by exercise and stress [193,194], conditions that also modify the gut microbiota [195,196]. It is important to note that more studies linking changes in PYY and the gut microbiota are needed.…”
Section: Microbiota and The Npy Pyy And Pp: Relevance To Anxiety Anmentioning
confidence: 99%
“…In homeotherms, including birds and mammals, modification of food intake by thermal stress ( 1 , 35 ) is typically associated with corresponding changes in orexigenic/anorexigenic signals in the brain as well as in peripheral tissues (e.g., GI tract and adipose tissue) ( 2 , 3 , 36 ). In mammals (e.g., rat), the central effects of thermal regulation are commonly accepted to be mediated by the temperature-sensitive neurons within the hypothalamus ( 37 ), presumably via activation of thermo-TRP ion channels ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature change in the environment is a key factor known to affect energy metabolism ( 1 ) and body growth in animals ( 2 ), and these modulatory effects are partly mediated via regulation of food intake ( 3 ). In fish models, circannual rhythm of feeding pattern and food intake has been reported, which is under the influence of environmental cues including seasonal change in water temperature ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 11 of 12 participants exhibited higher energy intake following WBC treatment, which suggests that inter-individual variation in the orexigenic impact of post-exercise WBC was substantially minor. We hypothesized that increased energy intake after WBC would be explained by transient changes in appetite-regulating hormones, as these hormones (e.g., ghrelin, leptin) were previously associated with augmented appetite and energy intake in cold environments [ 17 , 18 , 19 , 31 ]. Tomasik et al [ 18 ] demonstrated that cold exposure (2 °C) caused higher total ghrelin concentrations compared with neutral (20 °C) and hot environments (30 °C).…”
Section: Discussionmentioning
confidence: 99%